Ethanol consumption aggravates amyloid pathology and neuroinflammation in Alzheimer’s disease associated with inflammasome activation and ASC speck propagation - Veronika Brezani; Radhika S. Joshi; Marti Ortega-Ribera; Prashanth Thevkar Nagesh; Viliam Brezani; Adam Zivny; Evelyn A. Kurt-Jones; Douglas T. Golenbock; Gyongyi Szabo (Journal of Neuroinflammation)
Abstract Background Alcohol use disorder (AUD) has been associated with Alzheimer’s disease (AD) and dementia, yet the underlying mechanisms and specific role of ethanol in AD progression remain poorly understood. Neuroinflammation has emerged as a key contributor to both AD pathogenesis and ethanol-induced brain damage. Activation of innate immune cells and signaling pathways, in particular NLRP3 inflammasome, plays a pivotal role in both AD and ethanol-induced inflammation. Thus, we postulated that excessive ethanol consumption could contribute to AD progression via amplified neuroinflammation. Methods The 12–15-month-old WT and APP/PS1 mice received water or ethanol (3.5 g/kg) binge every alternate day for a period of one month. The effects of ethanol on amyloid pathology, microglia and astrocyte activation, and NLRP3 inflammasome activation were evaluated in the mouse brains. The effect of ethanol and amyloid β on NLRP3 inflammasome signaling was further studied in primary glial cells. Results In this study, we show that repeated ethanol binges aggravate the amyloid pathology and plaque burden in the hippocampus of APP/PS1 mice. Furthermore, we demonstrate the additive effect of ethanol administration on NLRP3 inflammasome activation, IL-1β release, and ASC aggregation in the brains of APP/PS1 mice and primary glia cultures. Our study also reveals a strong astrocyte activation by ethanol in the hippocampus of APP/PS1 mice as demonstrated by significantly increased GFAP and ALDH1L1 protein levels. Further in vitro analysis revealed that ethanol potentiates the effect of amyloid β to increase the NLRP3 inflammasome activation in both primary astrocytes and microglia. Lastly, we demonstrate that glia-produced ASC specks induce IL-1β in microglia and astrocytes and induce ROS in SH-SY5Y neurons, contributing to sustained neuroinflammation in AD. Conclusion Collectively, our results demonstrate that ethanol consumption exacerbates features of AD pathology associated with amplified neuroinflammation and NLRP3/ASC inflammasome activation, which may play an important role in the disease progression and severity.